1996
DOI: 10.21273/jashs.121.4.599
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation-induced Variation in Carrots (Daucus carota L.)

Abstract: Carrot tissue cultures, germinating seed, and dry seed were exposed to gamma radiation. Irradiation accelerated germination of carrot seed in the M1 generation at low doses (0.5 and 1 krad), whereas higher doses delayed germination. A high negative correlation was observed between dose and survival of plants after seed irradiation. Plant size and root weight were 20 % to 35% greater than control plants after seeds, but not tissue cultures, were exposed to low doses of gamma irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 26 publications
(25 reference statements)
2
10
0
1
Order By: Relevance
“…1, 2, 3, 4 and 5. Survival of P.corylifolia at higher doses (10 kGy) highlight its great radio resistance, compared to other species such as Pisum sativa (Zaka et al 2004) and carrot (Al-Safadi and Simon 1996) where gamma irradiation with 10 and 200 Gy respectively led to 50% inhibition of first generation plantlet growth. The growth inhibition was parallel to increment in psoralen at all phenological stages at same dosage (20 kGy) particularly in flowering stage.…”
Section: Discussionmentioning
confidence: 96%
“…1, 2, 3, 4 and 5. Survival of P.corylifolia at higher doses (10 kGy) highlight its great radio resistance, compared to other species such as Pisum sativa (Zaka et al 2004) and carrot (Al-Safadi and Simon 1996) where gamma irradiation with 10 and 200 Gy respectively led to 50% inhibition of first generation plantlet growth. The growth inhibition was parallel to increment in psoralen at all phenological stages at same dosage (20 kGy) particularly in flowering stage.…”
Section: Discussionmentioning
confidence: 96%
“…Low doses of γ-radiation have been reported to stimulate plant growth and development, and improve the yields and qualities of plants in vivo (Al-Safadi and Simon 1995, Wiendl et al 1995, Paull 1996 and in vitro (Degani andPickholz 1973, Al-Safadi andSimon 1990), apart from its induction of mutants in flower colour and shape (Misra et al 2003).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Researchers like Estramareix et al (1986) LoSchiavo et al (1989, Sung (1976) and Templeton-Somers et al (1981) have studies on carrot mutagenesis and most of the changes were observed at the molecular or cellular levels and not in whole plants. Al-Safadi and Simon (1996), exposed gamma radiation to carrot tissue cultures, germinating seed, and dry seed for their investigation. Irradiation accelerated germination of carrot seed in the M1 generation at low doses (0.5 and 1 krad), whereas higher doses delayed germination.…”
Section: Resultsmentioning
confidence: 99%